Coups, Regime Transition, and the Dynamics of Press Freedom - Christian Bjørnskov; Andreas Freytag; Jerg Gutmann (University of Hamburg, Institute of Law and Economics (ILE), 2018)
This paper explores the dynamics of press freedom around events that threaten or oust the incumbent regime of a country. While democracies on average grant the press more freedom, our theoretical starting point is that democracies and autocracies may have similar incentives to protect the power of the governing regime. A priori it is, nevertheless, not clear whether democracies or autocracies react more harshly – by silencing or controlling the media – to an attempt to overthrow the government. We estimate the dynamics of press freedom around both failed and successful coups and find that although press freedom is quite stable, successful coups lead to a substantial reduction in press freedom. This is, however, only the case when the coup is directed against a democratically elected government.
Keywords: D74; H12; L51; L82; 320; coup; political instability; press freedom